Political Rhetoric in Social Interaction: A Case Study of Ingrida Šimonytė’s Facebook Activity - Vaičekauskienė, Giedrė (Politologija, 2018)
[only abstract in English; full article, abstract in Lithuanian]This article analyzes the role of political rhetoric in social interaction with the public on the internet when considering public issues. Today Facebook, a new platform for political communication, is seen as a media platform where citizens are provided with abundant information about politics and society. During the transformation period, a political leader becomes the most important direct reporter for his electorate. The language of a politician is like the politician’s “product,” which is personally produced and sold in the “market of virtual society.” The language of a politician is their identity. As the media of social network is not editorial, the politicians themselves are responsible for the broadcast of personal rhetoric as well as telling and creating confidence in politics.This article presents a qualitative research. It includes the analysis of the rhetoric of Ingrida Šimonytė, a member of the Seimas of Lithuania of the 2016–2020 term, who is also a former Minister of Finance, while constructing her self-representation to the “friends” found on the social network on her personal Facebook account. During the research, it was established that Ingrida Šimonytė’s rhetoric on discussed public issues include the following topics: a) Criticism of personalities of the governing majority; b) Criticism of her colleagues – members of the Seimas; c) Tax, state treasury issues; d) Issues with the city of Vilnius. The way that issues are framed by the member of the Seimas provides a rich arsenal of rhetorical arguments: ranging from authentic sentences to rough, non-standard vocabulary. The verbal ethos of Ingrida Šimonytė as a speaker is ironic, and the shared information of private nature is also full of auto-irony.
Keywords: none